Electroactive Polymer Actuators and Devices (EAPAD) XXIII (SPIE / International Society for Optical Engineering, 2021)
Proceedings of SPIE offer access to the latest innovations in research and technology and are among the most cited references in patent literature. The papers in this volume were part of the technical conference on Electroactive Polymer Actuators and Devices (EAPAD) XXIII held on 22-26 March 2021 Online Only, United States.
Keywords: Conducting polymers.; Conducting polymers -- Congresses.; Polymers -- Electric properties.; elektronické knihy; electronic books